Kepemimpinan "Hulu Apad" Desa Pakraman Tinggan Ditinjau dari Sistem Demokrasi Pancasila - I Wayan Suarjaya (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
AbstractHulu Apad Leadership is a Bali traditional organization which develops sporadically in Hindu communities, especially in the mountain areas. This writing assesses the hulu apad system viewed from the Indonesia democratic system. The Pancasila democratic system in hulu apad system at Tinggan village, Pelaga, Petang, Badung is described on this writing. Description of determination process of hulu apad system, the main duties and functions of each person in-charge (prajuru hulu apad) in Tinggan Village. In real life, the hulu apad leadership is in line with the value of Pacasila democratic system, especially at the election of the person in-charge or the leader of the organization (Singukan), in which the leader is elected by the community, from the community and for the community. Once a leader is elected, his/her work ethic will implement the consensus system, collective works/cooperation and respect other’s rights based on the traditional/local laws regulated in the community (awig-awig).